2014
DOI: 10.1016/j.joen.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biocompatibility and Oxidative Stress Profiles of Different Hydraulic Calcium Silicate Cements

Abstract: Introduction MTA Plus (MTAP; Avalon Biomed Inc., Bradenton, FL) is a new calcium silicate cement with unknown cytotoxicity characteristics. The objectives of this study were to examine the effect of MTA Plus on the viability, apoptosis/necrosis profile and oxidative stress levels of rat odontoblast-like cells. Methods MDPC-23 cells were exposed to gray and white MTA Plus (GMTAP, WMTAP), gray and white ProRoot® MTA (GMTA, WMTA; Dentsply Tulsa Dental Specialties, Tulsa, OK) cements or their eluents. The cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 30 publications
6
26
0
Order By: Relevance
“…They are also consistent with a study included in the XTT assay that MTA Plus with 1 : 5 and 1 : 10 dilutions had no toxic effects on MDPC‐23 cells (Eid et al . ).…”
Section: Discussionmentioning
confidence: 96%
“…They are also consistent with a study included in the XTT assay that MTA Plus with 1 : 5 and 1 : 10 dilutions had no toxic effects on MDPC‐23 cells (Eid et al . ).…”
Section: Discussionmentioning
confidence: 96%
“…To avoid the initial cytotoxic effects of TSCs as demonstrated in a previous study [26], a previously-published aging/elution protocol based on the cements' specific cytotoxic profiles was adopted to render the cement discs non-cytotoxic prior to initiation of the experiment [26, 27]. According to this protocol, cement discs were sterilized by UV light for 4 hours, aseptically placed in their respective sterile Transwell® inserts (3.0 micron porous filter, Corning Inc., MA), and immersed in complete culture medium (CCM) for 2 weeks at 37°C in 100% humidity.…”
Section: Methodsmentioning
confidence: 99%
“…Histological assessment of them indicated that although both materials were well tolerated, supported cell attachment, proliferation and matrix formation, more inflammation was associated with WMTA (Vosoughhosseini et al, ). Using MDPC‐23 cells and XTT assay, GMTA had higher cell viability than WMTA (Eid et al, ).…”
Section: Introductionmentioning
confidence: 99%